Key Forwarding and Vehicle Parking Using IOT - Dr.D.K.Nayana, Vinay, Yashwanth K S, Arun Kumar M , Shivaraja S B (International Journal of Advanced Science and Technology, 2020)
If all the electronic things start to talk with each other and able to take its own decision, this can be doneby using these IOTs here we are communicating with a vehicle through the mobile for keyforwarding.In automatic gate control, it automatically controls all the activities of the gate and displays the free slots available at the parking. sometimes, in the parking lot it is very difficult to find the place for our vehicle, we have an idea for this problem. Using Arduino, we are learning so many things. Today due to the increase in vehicle, there is a lot gathering of the traffic at the parking area of malls and apartments. The main reason for this traffic at the parking area is due to the manual working of the amount collection at the area. we decided to work on to build the project which reduce the manual work and hence increase the vehicle speed passing by the booths.